PENERAPAN PEMBELAJARAN E-PEDAGOGY PADA MATA PELAJARAN KKPI DI SEKOLAH MENENGAH KEJURUAN - Mangesa, Riana T (Indonesian Journal of Educational Studies, 2015)
This study aims to determine the effectiveness of the application of the principles of elearning on subjects Pedagogy Keterampilan Komputer dan Pengelolaan Informasi (KKPI). This research is a classroom action research (PTK) whose implementation procedures; planning, action, observation and reflection. The results obtained with the testing techniques, observation and documentation. The analysis technique using descriptive statistics The results showed with the principles of e-learning Pedagogy is effective on subjects KKPI, SMK Negeri 1 Pallangga